Texture Properties, Water Activity, Emulsion Stability, and Microstructure of Beef Sausage with the Addition of Papaya Peel Flour - Evanuarini, Herly; Susilo, Agus; Rahayu, Premy Puspitawati (Faculty of Animal Science Universitas Brawijaya, 2025)
Growing interest in sustainable food production has led to the exploration of fruit and vegetable by-products as functional ingredients in meat products. This study investigates the effects of papaya peel flour on the texture, water activity (Aw), emulsion stability, and microstructure of beef sausages. Papaya peel flour, which is rich in dietary fiber, was added at various percentages (0.1%, 0.2%, and 0.3%) to determine its effect on sausage quality. Beef sausages were formulated with different levels of papaya peel flour, and their quality attributes were assessed using texture analysis, water activity measurement, emulsion stability tests, and scanning electron microscopy (SEM). Sausages were produced using beef treated with papaya peel flour and control. The results showed that the addition of papaya peel flour at 0.3% improved texture, to an optimal level without compromising sensory acceptability. Water activity decreased significantly at higher addition levels, which was beneficial in improving microbial stability. Emulsion stability was improved with the addition of papaya peel flour, due to its capacity to bind water and retain fat. SEM analysis showed a well-integrated fiber distribution at 0.3%, which contributed to the structural integrity. Papaya peel flour has the potential as a filler in meat product formulations. Optimization of waste products contributes to an environmentally friendly food system and opens up possibilities for applications in the food sector.